Education policies, school organization and the work of teachers - Licínio C. Lima (Universidade Estadual Paulista Júlio de Mesquita Filho, 2011)
Big changes in the state´s role in public education policies have occurred throughoutthe last decades by the action of transnational and supranational entities. An increasing process of subordination of education to economic imperatives in late capitalism and to entrepreneurial theories of school organization and leadership hasfollowed. Some dimensions of what is called by the author the managerialist canonand the hyper-bureaucratization of schools are analyzed with reference to international tendencies and also to the most recent Portuguese reform of the management system of state schools. Possible impacts of the political and organization changes introduced are suggested for future research, mainly concerning the working process of teachers and the tendencies towards competitiveness, deprofessionalization, subordination and alienation.